Digital platform for video-based agricultural extension in Ethiopia - CGIAR Research Program on Policies, Institutions, and Markets (2019)
The Government of Ethiopia launched “Digitalizing Agricultural Advisory Services” - a country-wide project that aims to create a digital platform for video-mediated agricultural advisory services for smallholders. IPIM research played a key role in providing critical evidence on the benefits of video-mediated extension.